Tobacco cv. Solaris seed cake as feed for light lambs: growth performance, carcase traits and meat quality - Antonella Fatica; Marisa Palazzo; Siria Tavaniello; Meng Peng; Dereje Birara Teshale; Giuseppe Maiorano; Elisabetta Salimei (Italian Journal of Animal Science)
Sixteen crossbred male lambs, housed in eight pens, were fed two isoenergetic and isonitrogenous diets: Control (CTR; n = 8) and Nicotiana tabacum cv. Solaris seed cake (SSC; n = 8). During the trial, lasted 35 days, pen dry matter (DM) concentrate consumption was calculated, individual body weight recorded, and average daily gain (ADG) calculated. Physico-chemical analyses were carried out on samples of Longissimus dorsi (LD) and Semimembranosus (SM) muscles. Animals fed Solaris seed cake showed lower (p < 0.05) ADG and slaughter body weight than CTR group. Diet did not affect the DM concentrate consumption. CTR lambs had higher cold carcase weight and yield (p < 0.01), while the proportion of commercial cuts did not differ between groups. Diet did not affect meat colour; the pH was higher (p < 0.01) for SSC group. Meat total lipid, collagen and cholesterol contents were unaffected by the diet. Fatty acid composition showed lower palmitic acid (C16:0, p < 0.05) and higher stearic acid (C18:0, p < 0.01) content in SSC compared to CTR fed lambs. The LD muscle showed lower total lipid (p < 0.01) and collagen content (p < 0.05) than SM muscle, as well as higher proportion of total SFA (p < 0.01) and lower proportion of total PUFA (p < 0.01), n-3 PUFA (p < 0.05) and n-6 PUFA (p < 0.01). Further studies are needed for a better evaluation of the potential of the innovative tobacco Solaris co-product in lambs’ diet.